Moderating Avoidance Performance Goal Orientation Withdrawal Through Individuated Assessments and Common Affiliation. (April 2021) - Kraemer, Justin; Gunkel, Marjaana; Chung, Ken
Scholars have long assumed that members of small groups are more likely to help each other. We argue that, even in a small group with collective rewards, those with an avoidance performance goal orientation, a dispositional fear of inadequate performance, would view social interaction as more disadvantageous and, as a result, help their group less. Using random coefficient modeling, we also demonstrate that the strength of the individual-specific assessment of reliance on and a category-specific common affiliation with group members reduce this negative association. We discuss theoretical and practical implications and conclude by identifying limitations of our study and offer directions for future investigation.